A comparison of ISIS foreign fighters and supporters social media posts: an exploratory mixed-method content analysis. (1st October 2020) - Dillon, Leevia; Neo, Loo Seng; Freilich, Joshua D.
ABSTRACT: This paper compares the social media posts of ISIS foreign fighters to those of ISIS supporters. We examine a random sample of social media posts made by violent foreign fighters ( n  = 14; 2000 posts) and non-violent supporters ( n  = 18; 2000 posts) of the Islamic State of Iraq and Syria (ISIS) (overall n  = 4, 000 posts), from 2009 to 2015. We used a mixed-method study design. Our qualitative content analyses of the 4, 000 posts identified five themes: Threats to in-group, societal grievances, pursuit for significance, religion, and commitment issues. Our quantitative comparisons found that the dominant themes in the foreign fighters' online content were threats to in-group, societal grievances, and pursuit for significance, while religion and commitment issues were dominant themes in the supporters' online content. We also identified thematic variations reflecting individual attitudes that emerged during the 2011–2015 period, when major geopolitical developments occurred in Syria and Iraq. Finally, our quantitative sentiment-based analysis found that the supporters (10 out of 18; 56%) posted more radical content than the foreign fighters (5 out of 14; 36%) on social media.